2004
DOI: 10.1016/j.jpainsymman.2004.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of skeletal muscle relaxants for spasticity and musculoskeletal conditions: a systematic review

Abstract: Skeletal muscle relaxants are a heterogeneous group of medications used to treat two different types of underlying conditions: spasticity from upper motor neuron syndromes and muscular pain or spasms from peripheral musculoskeletal conditions. Although widely used for these indications, there appear to be gaps in our understanding of the comparative efficacy and safety of different skeletal muscle relaxants. This systematic review summarizes and assesses the evidence for the comparative efficacy and safety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
149
0
30

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(181 citation statements)
references
References 94 publications
(120 reference statements)
2
149
0
30
Order By: Relevance
“…13,14 A prior systematic review of the comparative and efficacy and safety of skeletal muscle relaxants for treatment of spasticity among patients with diverse neurologic impairments revealed equivalent efficacy of baclofen and tizanidine with a higher frequency of dry mouth with tizanidine and more weakness with baclofen. 15 A recent systematic review of stretching efficacy indicated inconclusive evidence regarding its efficacy for spasticity reduction. 16 Quantitative assessment of spasticity (both relative and absolute) is vital to the detection of spasticity among individuals with SCI and determination of treatment efficacy in a clinical trial setting or effectiveness in the clinic setting.…”
Section: Spasticity Treatmentmentioning
confidence: 99%
“…13,14 A prior systematic review of the comparative and efficacy and safety of skeletal muscle relaxants for treatment of spasticity among patients with diverse neurologic impairments revealed equivalent efficacy of baclofen and tizanidine with a higher frequency of dry mouth with tizanidine and more weakness with baclofen. 15 A recent systematic review of stretching efficacy indicated inconclusive evidence regarding its efficacy for spasticity reduction. 16 Quantitative assessment of spasticity (both relative and absolute) is vital to the detection of spasticity among individuals with SCI and determination of treatment efficacy in a clinical trial setting or effectiveness in the clinic setting.…”
Section: Spasticity Treatmentmentioning
confidence: 99%
“…Os relaxantes musculares comercializados no país são de diferentes classes químicas do nível 4 da ATC, mas considerando o emprego terapêutico abrangem dois grupos, o do baclofeno, tizanidina, tiocolchicosídeo empregados em condições espásticas como esclerose múltipla, lesão de medula espinhal e paralisia cerebral; o outro grupo de fármacos é representado pelo carisoprodol, ciclobenzaprina, clorzoxazona e orfenadrina, empregados em condições musculoesqueléticas como lombalgias 12,35,36 .…”
Section: Discussionunclassified
“…As indicações clínicas dos relaxantes musculares são fundamentadas em evidências científicas limitadas por causa de delineamentos metodológicos de baixa qualidade, métodos de avaliação insensíveis e inclusão de número reduzido de pacientes nos ensaios clínicos 12,35,37 . É preocupante a ausência de estudos clínicos avaliando a eficácia de relaxantes musculares nos diferentes grupos etários 35 , principalmente considerando que nos Estados Unidos estima-se que aproximadamente 2 milhões de pessoas por ano usam relaxantes musculares, principalmente para lombalgia, sendo que cerca de 300.000 dos usuários são idosos 12 .…”
Section: Discussionunclassified
See 2 more Smart Citations